Antibiotic susceptibility of Staphylococcus aureus and Escherichia coli isolated from dairy goats in selected farms in Selangor, Malaysia - Mansor, Rozaihan; Diauudin, Naseeha Sakina; Syed Hussain, Sharifah Salmah; Khalid, S. F. (Veterinary Association Malaysia, 2019)
Antimicrobial resistance (AMR) has become a major problem worldwide with significance public health impact in both animal and human populations. Staphylococcus aureus (S. aureus) is a common pathogen in domestic livestock and Escherichia coli (E. coli) is a normal flora in the gut and these organisms are considered as effective indicators for AMR surveillance. Increased in antimicrobial resistance of these bacteria in veterinary medicine leads to difficulties in choosing effective antibiotics to treat diseases they caused. This study aimed to evaluate the susceptibility of S. aureus and E. coli isolated from dairy goats in selected farms located in Selangor, Malaysia against different antibiotics. Milk and faecal samples were collected from 36 dairy goats and samples were prepared for the isolation of S. aureus and E. coli isolates respectively. The isolates were subjected to antibiotic susceptibility test. All 11 (100%) E. coli isolates showed resistance to amoxicillin and penicillin while 3 (27%) of the 11 S. aureus isolates, showed resistance towards the same class of antibiotic. Both S. aureus and E. coli isolates showed high susceptibility to four antibiotics, namely trimethoprim-sulfamethazole, neomycin, tetracycline and enrofloxacin. This study provided information regarding the antibiotic resistance of S. aureus and E. coli in relation to the antimicrobial usage practice in selected dairy goat farms located in Selangor, Malaysia.